Endovascular therapy for acute stroke: Quo vadis? - Venkatesh S. Madhugiri; Paritosh Pandey (Indian Journal of Neurosurgery)
Endovascular therapy (EVT) has gained vogue in the management of patients with acute stroke. Newer stent-retriever devices have led to better recanalization rates. In many centers, EVT is slowly being used as an add on to or in some instances, even as an alternative to intravenous tissue plasminogen activator (IV tPA). The publication of the results of the SYNTHESIS expansion, Interventional Management of Stroke III and Mechanical Retrieval Recanalization of Stroke Clots Using Embolectomy trials in 2013 has questioned the enthusiastic use of EVT in acute stroke. They demonstrate that EVT (using a variety of devices) is no superior to IV tPA in the management of acute stroke. In the light of these controversial findings, we review the current status of EVT in the management of acute stroke.